Influence of the Surface on the Atmospheric Circulation of Mars: Study with a General Circulation Model - Saito, Ryu (2006)
Unlike on Earth where 3/4 of the surface is covered by oceans, the Martian surface has a topography with greater magnitudes of mountains and valleys. This and other differences indicate that the Martian atmosphere should be very sensitive to the forcing from below. The major mechanism which provides vertical coupling are atmospheric waves generated in the lower atmosphere near the surface. They transport momentum, energy, and heat away from the lower atmosphere. Propagating upward the disturbances grow in amplitude, and ultimately break or dissipate. They release energy and momentum to the zonal mean circulation, and affect the global transport in the atmosphere of Mars. The main task of this work is to study these physical phenomena in the atmosphere near the surface with an emphasis on the mechanisms of wave generation. Effects of large scale longitudinal disturbances on the general circulation, especially in the upper and middle atmosphere, are explored. Results of numerical experiments with a General Circulation Model of the Martian Atmosphere show the sensitivity of the zonal mean circulation to the surface properties. Planetary waves of different scales are generated over the topography as well as by the inhomogeneous reaction of the surface and the lower atmospheric layers to the solar heating. Solar tides are excited as well. These large scale disturbances propagate upward and horizontally according to the selective transmission properties of the atmosphere, and redistribute momentum and energy. Breaking waves provide a torque to the mean zonal wind and maintain the global meridional transport. The results of the numerical simulations showing the sensitivity of the polar night jet to the topography, the inhomogeneous thermal inertia and the surface albedo, are presented here. To validate the simulations, the results are compared with observations from the Thermal Emission Spectrometer onboard the Mars Global Surveyor. Der Mars verfügt im Vergleich zur Erde, bei der 3/4 der Oberfläche mit Ozeanen ...